pengaruh penggunaan LKPD berbasis STEM terhadap hasil belajar pengetahuan, sikap dan keterampilan siswa kelas VI SD materi pubertas - Lestari, Yuni; Widi Winarni, Endang; Susanta, Agus (UNIB Press, 2024)
This study aims to determine the effect of using STEM-based worksheets on learning outcomes of knowledge, attitudes and skills of sixth grade elementary school students on puberty. This research is a quantitative research. The method used is a quasy experiment. The design in this study is The Matching Only Pretest-Posttest Control Group Design. The population in this study were students of class VI SDN 33 with a total of 30 students as the experimental class and class VI of SDN 29 as many as 27 students as the control class. The instrument given was in the form of a written test consisting of knowledge, attitude and skills variables. The results showed that there was a significant effect of the use of STEM-based worksheets on the learning outcomes of knowledge, attitudes and skills of sixth grade elementary school students on puberty.